STUDI POTENSI PENGOMPOSAN SAMPAH KOTA SEBAGAI SALAH SATU ALTERNATIF PENGELOLAAN SAMPAH DI TPA DENGAN MENGUNAKAN AKTIVATOR EM4 (EFFECTIVE MICROORGANISM) - Budihardjo, Mochamad Arief (Universitas Diponegoro, 2006)
In general, waste management in most of City in Indonesia still boundary on collecting, transporting and dumping. Solid waste are collected, transported and pulled up in landfill without any treatment. Needed a new paradigm that landfill is not a final estuary of city waste but place management of city waste. One of the problem faced is amount arise of organics city waste. Starting from this situation hence needed handling to arising organic waste. Composting represent one of the alternative in the effort to reduce the amount of organics city waste through the make up of value utilize waste become worthwhile compost as fertilizer. Natural composting of organics waste took a time to process. Effective microorganism (EM4) applicated in organics waste composting in landfill is used to speed up compost decomposition and improve the compost quality. Composting use all kinds of city waste that enter to the landfill, like residue of vegetables, fruits, leaves and sawmill waste. Composting city waste wrap up addition material that is sawdust and cow manure. At this research, compost variation include natural control variation, organic waste and EM4, organic waste : sawdust and EM4 with comparation 7:3; 1:2; 5:7; 5:4 and 7:6. Organic waste: cow manure and EM4 with comparition 1:2; 2:5; 6:5 and 7:6. Result of this research indicate that the overall compost variation has fulfilled standard of quality matured compost according to SNI 19-7030-2004t. Compost with EM4 has relative good quality than natural compost. Besides, overall of compost variation have fulfilled hara standard of crop requirements, low cost of producing and yield high level of city waste reducing. Compost variation of 7 organic city waste : 3 sawdust represent most applicable composition compost at Boyolali landfill with C-organic 24,52 %, N-total 1,72 %, Ratio C/N 14,25, P-total 1,20 %, K-total 1,66 %, Temperature 27,70 0C and pH 7,30 also compost level reduction 61,6 %.